Class fictions : shame and resistance in the British working-class novel, 1890-1945 - Fox, Pamela, 1958- (Post-contemporary interventions., 1994)
Many recent discussions of working-class culture in literary and cultural studies have tended to present an oversimplified view of resistance. In this groundbreaking work, Pamela Fox offers a far more complex theory of working-class identity, particularly as reflected in British novels of the late nineteenth and early twentieth centuries. Through the concept of class shame, she produces a model of working-class subjectivity that understands resistance in a more accurate and useful way-as a complicated kind of refusal, directed at both dominated and dominant culture. With a focus on cer.